Evaluation of mongrel sires in the dry tropics under extensive exploitation conditions as a predictor of the bull / cow relationsh - Macías Moreira, Yandri Andrés (2020)
The objective of the study was to evaluate the reproductive condition of mestizo bulls in the dry tropics under conditions of extensive exploitation, analyzing semen quality and other reproductive characteristics associated with fertility. The investigation was carried out between September and October, in the Rocafuerte canton located in the dry tropical zone of the province of Manabí, Ecuador. Sixty mongrel bulls of different racial crosses and ages were evaluated, under natural riding conditions and without sexual rest, before the exam. Semen samples were obtained by electro ejaculation, with minimal impact on the well-being of bulls. In the evaluation of the primary organs a scrotal circumference of 33,1 cm was observed, the highest range being 39,5 cm and a minimum of 28 cm. It was found that 75 % of bulls are within the parameters for natural riding due to the concentration and sperm normality of good to very good. In addition, 68,33 % had a sperm concentration higher than the minimum standard, it could be established that bulls are riding cows at a 5 % ratio regardless of service capacity. Therefore, the application of the andrological examination is important as a predictor of the bull/cow relationship in natural mounts and to rule out bulls with subfertility problems, improving the reproductive efficiency of the stallion, having a great socioeconomic impact on the livestock sector of the region from the Ecuadorian coast.